2012
DOI: 10.1038/bjc.2012.360
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic utility of pre-operative circulating osteopontin, carbonic anhydrase IX and CRP in renal cell carcinoma

Abstract: Background:Objectively measured circulating biomarkers of prognosis complementing existing clinicopathological models are needed in renal cell carcinoma (RCC).Methods:Blood samples collected from 216 RCC patients in Leeds before nephrectomy (median follow-up 7 years) were analysed for C-reactive protein (CRP), osteopontin (OPN) and carbonic anhydrase IX (CA9) and prognostic significance determined.Results:CA9, OPN and CRP were univariately prognostic for overall survival (OS), cancer-specific survival (CSS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…Specifically, the SSIGN score is often grouped into three categories, which results in a loss of granularity as demonstrated by a reduction in the reported C - index for SSIGN alone, and thus an apparent incremental gain in the C-index when combined with new biomarkers [28,29], which may not exceed that of the SSIGN when used as described.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the SSIGN score is often grouped into three categories, which results in a loss of granularity as demonstrated by a reduction in the reported C - index for SSIGN alone, and thus an apparent incremental gain in the C-index when combined with new biomarkers [28,29], which may not exceed that of the SSIGN when used as described.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma CRP levels are also associated with an increased risk of cancer [24-27], but causality has not been established. High levels of circulating CRP have also been linked to advanced disease and a poor prognosis in various malignancies, including oral and esophageal SCC [6-8], lung cancer [9,10], melanoma [11], hepatocellular carcinoma [12,13], breast cancer [14], endometrial cancer [15], renal cell carcinoma [16,17], urothelial carcinoma [18], and castration-resistant prostate cancer [19,28]. This study shows for the first time that elevated preoperative CRP levels are also associated with penile cancer stage, but not grade.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear whether the tumor promotes inflammation or is rendered more aggressive by it. High levels of circulating CRP have recently been linked to poor prognosis in various malignancies, including oral SCC [6], esophageal SCC [7,8], non-small cell lung cancer [9], small cell lung cancer [10], melanoma [11], hepatocellular carcinoma [12,13], breast cancer [14], endometrial cancer [15], renal cell carcinoma [16,17], urothelial carcinoma [18], castration-resistant prostate cancer [19], and even diffuse large B cell lymphoma [20]. There have been conflicting reports about the correlation between CRP and prognosis in patients with colorectal cancer [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 43 eligible studies (7, 490 patients) were identified for this meta-analysis (25 for RCC (Atzpodien et al, 2003;Bromwich et al, 2004;Casamassima et al, 2005;Peccatori et al, 2005;Ito et al, 2006;Lamb et al, 2006;Vogl et al, 2006;Karakiewicz et al, 2007;Komai et al, 2007;Ramsey et al, 2007;Kawata et al, 2008;Ramsey et al, 2008;Tanaka et al, 2008;Iimura et al, 2009;Jagdev et al, 2010;Cho et al, 2011;Falkensammer et al, 2011;Bedke et al, 2012;Fujita et al, 2012;Sim et al, 2012;Steffens et al, 2012;de Martino et al, 2013;Yasuda et al, 2013), 10 for UC (Hilmy et al, 2005;Hilmy et al, 2006;Saito et al, 2007;Yoshida et al, 2008;Gakis et al, 2011;Saito and Kihara, 2011;Ishioka et al, 2012;Obata et al, 2012;Tanaka et al, 2012;Stein et al, 2013), and 8 for PC (McArdle et al, 2006;Beer et al, 2008;Nakashima et al, 2008;McArdle et al, 2010;Pond et al, 2012;Prins et al, ...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%